Product design of upper sandal fabric cutting machine using ergonomic function deployment method - Wibisono, Aldino; Tranggono, Tranggono (Operations Excellence: Journal of Applied Industrial Engineering, 2023)
In the production process, the upper sandal cutting of KUB Mampu Jaya is still done manually using scissors one by one for each mold. The purpose of this research is to create an ergonomic upper sandal cutting machine. The method used in this research is Ergonomic Function Deployment (EFD). Direct data collection involved observing the production stages and activities carried out by workers through interviews and surveys. The results show that this sandal upper cutting machine has been designed by adjusting user needs so as to minimize production time and the cutting process becomes more efficient. Previously, the production or cutting time took 2 minutes per one upper sandal mold, but with this new cutting machine, the cutting process only takes 1 minute per upper sandal mold, saving up to 1 minute. The results of this study will provide a better solution in designing a sandal upper fabric cutting machine that prioritizes ergonomic aspects and can reduce musculoskeletal complaints.